(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2024)
In this article, the author points out the need to build a bridge between industrial centers, technologies and the educational process, to equip educational centers and to implement the idea of laboratories equipped with the necessary equipment. According to the researcher, students will be able to combine their theoretical knowledge with practical experience and develop the spirit of creativity and innovation.